Parallel Connected Dual-Mode Filter - Cheab, S. (Institute of Electrical and Electronics Engineers Inc., 2015)
Theory of parallel connected dual pole topology is introduced in this letter. The general transfer function of N transversal array is derived where the filtering function is mapped to Chebyshev polynomial in which all the coupling values are extracted. To demonstrate the feasibility of the approach two 2-stage bandpass dual mode filter prototypes based on parallel connected topology are fabricated and presented. The second filter prototype is incorporated with the source-load coupling in order to achieve a quasi-elliptic response for better selectivity. Â© 2001-2012 IEEE.